2015
DOI: 10.1111/papt.12083
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, depression and autonomy–connectedness: The mediating role of alexithymia and assertiveness

Abstract: The study confirmed the relevance of autonomy-connectedness in anxiety and depression. In treating symptoms of anxiety, it is advisable to give attention to normalizing the patient's sensitivity to others. Treatment of patients with symptoms of anxiety and depression should include assessment of emotional awareness and, in the case of impaired emotional awareness, should be tailored as to promote increased awareness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 86 publications
(103 reference statements)
2
15
0
1
Order By: Relevance
“…All items are measured with 5-point scales ranging from disagree to agree. 18,19 Internal consistency in this study was good, with a values of .81, .82, and .80, respectively.…”
Section: Autonomy-connectednessmentioning
confidence: 51%
See 1 more Smart Citation
“…All items are measured with 5-point scales ranging from disagree to agree. 18,19 Internal consistency in this study was good, with a values of .81, .82, and .80, respectively.…”
Section: Autonomy-connectednessmentioning
confidence: 51%
“…It consists of 30 items divided into 3 subscales: Self‐Awareness (7 items [eg, “I often do not know what my opinion is”]), Sensitivity to Others (17 items [eg, “I often wonder what other people think of me”]), and Capacity for Managing New Situations (6 items [eg, “I quickly feel at ease in new situations”]). All items are measured with 5‐point scales ranging from disagree to agree 18, 19. Internal consistency in this study was good, with α values of .81, .82, and .80, respectively.…”
Section: Methodsmentioning
confidence: 66%
“…The literature review showed that alexithymia, mental health and mobile phone addiction are correlated with each other. A previous study has shown that alexithymia could mediate the association between self-awareness and anxiety as well as depression [ 26 ]. Alexithymia is closely and positively correlated with chronic pain, and negative affects, including depression and anxiety symptoms, mediate this relationship [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The idea of dissociation within the emotion schemas can be applied to alexithymia; ‘without linkages to images and words, the individual is unable to symbolize emotional states’ (Taylor & Bagby, ; p. 105). Moreover, activation of the subsymbolic system without symbolic connections may result in poorly regulated states of emotional arousal, which may contribute to the pathogenesis of different disorders, both somatic (Chatzi et al ., ; Conrad, Schilling, Langenbuch, Haidl, & Liedtke, ; Korkoliakou et al ., ; Martínez et al ., ; Vanheule, Vandenbergen, Verhaeghe, & Desmet, ; Verissimo, , ) and psychiatric (Carano et al ., ; Caretti & Craparo, ; Carpenter & Chung, ; De Panfilis, Ossola, Tonna, Catania, & Marchesi, ; Kessler, Schwarze, Filipic, Traue, & Von Wietersheim, ; Li, Zhang, Guo, & Zhang, ; Ogrodniczuk, Sochting, Piper, & Joyce, ; Parker, Wood, Bond, & Shaughnessy, ; Pinaquy, Chabrol, Simon, Louvet, & Barbe, ; Rutten et al ., ), with which alexithymia has been associated (Solano, ; Taylor, ; Taylor & Bagby, ). However, the literature also indicates some rare studies that showed no differences between the scores of alexithymia obtained by clinical and general population measured with the TAS‐20 (Vinai et al ., ) or a non‐significant association between alexithymic characteristics measured with the TAS‐20 and a somatic or psychiatric disorder (Barbasio et al ., ; Kooiman, Bolk, Brand, Trijsburg, & Rooijmans, ).…”
Section: Introductionmentioning
confidence: 99%